Spatial Analysis of the Seismic Gap Zone Based on Multiparameter Seismotectonics in Southern East Java as an Indicator of Megathrust Earthquake Potential - Putri, Diva Maharani; Maharani, Nanda; Ilham, Ilham; Yulinda, Riska (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2025)
The southern region of East Java is located above an active subduction zone, where the Indo-Australian Plate is subducting beneath the Eurasian Plate. This tectonic condition makes the region potentially susceptible to large-scale megathrust earthquakes. This study aims to characterize the suspected seismic gap segments in the southern subduction zone of East Java, with a primary focus on the area between Pacitan and Lumajang. The approach used is based on high-resolution seismotectonic spatial analysis, combining three main parameters: seismicity distribution, earthquake return period estimates, and a-values and b-values as indicators of tectonic activity and stress condition. The analyzed data covers a long period of time, from 1910 to 2025, and was compiled by the BMKG and USGS catalogs. The results of the analysis show that the Pacitan-Lumajang segment experiences a lack of earthquake activity in the plate interface, although this area is tectonically active. In addition, this segment has a very long return period (> 500 years for Mw7 and > 4,000 years for Mw8), accompanied by low a-value and b-value, indicating low earthquake frequency and high stress accumulation. These findings indicate that the segment is a locked zone that has the potential to release large amounts of energy in the future. The results of this study provide an initial contribution in understanding the spatial distribution of seismic activity in the southern region of East Java, and can be used as supporting considerations in initial disaster risk assessments, especially in densely populated coastal areas.